The Role of Research in Wine: the Emergence of a Regional Research Area in an Italian Wine Production System - Andrea Morrison; Roberta Rabellotti (European Regional Science Association (ERSA), 2006)
The process of technological modernisation of the wine industry has increasingly become a global phenomenon involving both traditional wine producing countries – such as France, Italy and Portugal – as well as new emerging producers –as the US, Australia, South Africa, Chile and Argentina. At this respect, the literature (Aylward, 2003; Unwin, 1991) remarks that in the industry the process of technological renovation has been spurred by the consistent investment of new producer countries, as California, Australia, New Zealand and South Africa, in creating or strengthening research institutions. These efforts have led to the creation of a specialised wine research system. Conversely, it seems that producers in traditional wine producing areas have often been locked in old technologies and methods of production, due to path dependency. The aim of this paper is to shed some light on how old producing countries have reacted to the increased technological competition by emerging producers. In particular we focus on role played by research organisations (e.g. universities, public research centres) and intermediate institutions (e.g. sectoral associations, extension agencies, technological transfer centres) in generating and diffusing knowledge within the industry. The paper is based on first and second hand information collected in Piemonte, where it is located one of the most important Italian wine cluster. There, we have conducted an extensive fieldwork and interviewed several key informants working at research organisations; extension agencies, associations of producers and other associations acting as opinion/lobbying groups. The information collected are elaborated to reconstruct a detailed picture of actors, linkages and processes underpinning the regional innovation and production wine system.
Keywords: 330